Association between sleep duration and breast cancer incidence: The multiethnic cohort. Issue 3 (10th April 2019) - Shigesato, Maryssa; Kawai, Yosuke; Guillermo, Cherie; Youkhana, Fadi; Shvetsov, Yurii B.; Setiawan, Veronica W.; Haiman, Christopher A.; Le Marchand, Loïc; Maskarinec, Gertraud
Abstract : Breast cancer is the most common cancer and the second‐leading cause of cancer‐related death among women. Inconsistent findings for the relationship between melatonin levels, sleep duration and breast cancer have been reported. We investigated the association of sleep duration at cohort entry and its interaction with body mass index (BMI) with risk of developing breast cancer in the large population‐based Multiethnic Cohort study. Among the 74, 481 at‐risk participants, 5, 790 breast cancer cases were identified during the study period. Although we detected no significant association between sleep duration and breast cancer incidence, higher risk estimates for short (HR = 1.03; 95% CI: 0.97–1.09) and long sleep (HR = 1.05; 95% CI: 0.95–1.15) compared to normal sleep (7–8 hr) were found. The patterns for models stratified by age, BMI, ethnicity and hormone receptor status were similar but did not indicate significant interaction effects. When examining the combined sleep duration and BMI interaction effect, in comparison to the normal BMI‐normal sleep group, risk estimates for underweight, overweight and obesity were similar across categories of sleep duration (≤6, 7–8, and ≥9 hr). The underweight‐normal sleep group had lower breast cancer incidence (HR = 0.66, 95% CI: 0.50–0.86), whereas the overweight‐short sleep, overweight‐normal sleep group and all obese women experienced elevated breast cancer incidence. The respective HRs for short, normal and long sleep among obese women were 1.35 (95% CI: 1.20–1.53), 1.27 (95% CI: 1.15–1.42) and 1.46 (95% CI: 1.21–1.76). Future perspectives need to examine the possibility that sleep quality, variations in circadian rhythm and melatonin are involved in breast cancer etiology. Abstract : What's new? To date, the potential relationship between melatonin levels, sleep duration, and breast cancer remains unclear. This large ethnically diverse population‐based cohort study provides the first results on sleep duration and breast cancer among individuals of white, African American, Japanese American, Native Hawaiian, and Latino origin. Although sleep duration was not significantly associated with breast cancer incidence, the authors used a novel approach to examine the interaction effect of body mass index and sleep duration on breast cancer risk. In the combined BMI‐sleep analyses, participants with overweight or obesity had a higher breast cancer risk across all sleep categories.